1999
DOI: 10.1111/j.1469-7793.1999.0513v.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in properties and neurosteroid regulation of GABAergic synapses in the supraoptic nucleus during the mammalian female reproductive cycle

Abstract: GABAA receptor‐mediated synaptic innervation of oxytocin neurones in the supraoptic nucleus (SON) was analysed in adult female rats going through their first reproductive cycle by recording the spontaneous inhibitory postsynaptic currents (sIPSCs) at six stages of female reproduction. During pregnancy we observed a reduction in the interval between monoquantal sIPSCs. The synaptic current amplitude, current decay and neurosteroid sensitivity of postsynaptic GABAA receptors observed at this stage were not disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
104
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(114 citation statements)
references
References 42 publications
(114 reference statements)
10
104
0
Order By: Relevance
“…Initial reports indicated that a shift in the relative expression levels of GABA A receptor α 1 and α 2 subunit mRNAs in these neurons as female rodents transit from late pregnancy through parturition and to a lactating state results in a concomitant decrease in the sensitivity of these neurons to modulation by allopregnanolone, thus promoting disinhibition and enhanced firing of oxytocin neurons (Fénelon and Herbison, 1996a;Brussaard et al, 1997;Brussaard et al, 1999; for review Brussaard and Herbison, 2000;Herbison, 2001). While effects of antisense knockdown of α 2 subunit expression in neocortical slices demonstrated the expected acceleration of synaptic current decay kinetics (Brussaard et al, 1997), SON slices were not tested with anti-sense constructs, nor were antisense-treated cortical slices assayed for differences in the sensitivity to allosteric modulation by allopregnanolone to test directly if changes in α subunit expression resulted in concomitant changes in allopregnanolone potentiation.…”
Section: Steroid Modulation Of Reproductive Behaviorsmentioning
confidence: 99%
“…Initial reports indicated that a shift in the relative expression levels of GABA A receptor α 1 and α 2 subunit mRNAs in these neurons as female rodents transit from late pregnancy through parturition and to a lactating state results in a concomitant decrease in the sensitivity of these neurons to modulation by allopregnanolone, thus promoting disinhibition and enhanced firing of oxytocin neurons (Fénelon and Herbison, 1996a;Brussaard et al, 1997;Brussaard et al, 1999; for review Brussaard and Herbison, 2000;Herbison, 2001). While effects of antisense knockdown of α 2 subunit expression in neocortical slices demonstrated the expected acceleration of synaptic current decay kinetics (Brussaard et al, 1997), SON slices were not tested with anti-sense constructs, nor were antisense-treated cortical slices assayed for differences in the sensitivity to allosteric modulation by allopregnanolone to test directly if changes in α subunit expression resulted in concomitant changes in allopregnanolone potentiation.…”
Section: Steroid Modulation Of Reproductive Behaviorsmentioning
confidence: 99%
“…Allopregnanolone (5␣-pregnan-3␣-ol-20-one), abbreviated here as 3␣-OH-DHP, was obtained from Research Biochemicals and dissolved in DMSO at 10 mM and further diluted in external solution before application. The lipophylicity of this substance prevents accurate estimates of the final concentration of 3␣-OH-DHP at the site of action, as has been extensively discussed previously (4,5). Staurosporine, TPA (phorbol 12-myristate 13-acetate, PMA), and the inactive form of PMA, 4-␣-PMA, were all from Research Biochemicals and dissolved as stocks in DMSO at 10 mM.…”
mentioning
confidence: 99%
“…The spiking frequency of these neurons is under control of a GABAergic input (1)(2)(3). The postsynaptic ␥-aminobutyric acid type A (GABA A ) receptors that mediate this input are susceptible to allosteric interaction with the neurosteroid allopregnanolone 3␣-OH-DHP during some stages of the female reproductive cycle, in particularly during pregnancy (4,5). In addition, somatodendritic release of oxytocin within the SON acting on autoreceptors (6) decreases the fast synaptic inhibition of the magnocellular cells, via suppression of postsynaptic GABA A receptor activity in a Ca 2ϩ -dependent manner (7,8).…”
mentioning
confidence: 99%
See 2 more Smart Citations